The effect of Zataria multiflora and carvacrol on wheezing, FEV1 and plasma levels of nitrite in asthmatic patients - Azam Alavinezhad; Mahdiyeh Hedayati; Mohammad Hossein Boskabady (Mashhad University of Medical Sciences, 2017)
Objective: The preventive effect of Zataria multiflora in animal models of asthma has been reported. In the present study, its effect on wheezing, forced expiratory volume in 1 second, and plasma nitrite (NO2-) in asthmatic patients was studied. Materials and Methods: In this study, forty asthmatic patients including 15 males and 25 females (aged 45.8±6.21 years) were randomly allocated in four groups including placebo group (P), and three treatment groups which received two doses of Z. multiflora (groups Z low and Z high that received 5 and 10 mg/kg/day, respectively) and carvacrol (group C treated with 1.2 mg/kg/day). All patients were treated for two months in a double-blind manner. At three time points (before starting the treatment (pretreatment), and one and two month after treatment), wheezing during day and exercise, forced expiratory volume in 1 second and NO2- were measured. Results: Day wheeze and exercise wheeze were significantly reduced in treated groups with carvacrol and both doses of Z. multiflora compared to pretreatment (p1% was significantly increased in treated groups with carvacrol and both doses of Z. multiflora (p2- was also significantly decreased in Z high and carvacrol groups after two months of treatment (p Conclusion: Z. multiflora and its constituent, carvacrol, improved FEV1% while reduced wheezing and plasma level of NO2- in asthmatic patients. Therefore, a possible therapeutic potential for this plant and its constituent, carvacrol could be suggested to be used against asthma.